Cassava calling! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'Let s eat more cassava and cassava products!'. The President of the Association for the Integral Development of Women, in Dassa-Zoume in Benin, Mrs Pauline Dade Dagbede is full of praise for cassava.'Everyone knows that cassava is now our second...